FNAB and Anatomic Pathology Biopsy Accuracy in Thyroid Nodule Diagnosis - Muhammad Tegar Nugraha; Yohni Wahyu Finansah; Nova Primadina; Nurma Yuliyanasari (MAGNA MEDIKA: Berkala Ilmiah Kedokteran dan Kesehatan, 2022)
Background: The problem examined in this study is the accuracy of the FNAB examination compared to the gold standard histopathology.Objective: To determine the value of sensitivity, specificity, positive and negative predictive values , and the accuracy of the FNABMethod: This study uses a retrospective method. The population was patients with thyroid nodules in Pare Regional Hospital, Kediri, in 2015-2019. The sampling technique is Simple Random Sampling Probability. The sample was the patients who had been diagnosed with thyroid nodules and underwent FNAB examination followed by histopathology biopsy. The instrument used was secondary data collection inpatient medical record data. The data can be processed through diagnostic tests.Results: FNAB sensitivity value of 66.6%, a specificity value of 97%, a positive predictive value of 90.9%, and a negative predictive value of 86.8%, and an accuracy rate of 87.7%Conclusion: FNAB can be used as a first-line examination in diagnosing thyroid nodules but cannot replace histopathological examination as a gold standard.